Integrated Product and Process Development: Modular Production Architectures based on Process Requirements - Kampker, Achim; Burggräf, Peter; Deutskens, Christoph; Maue, Andreas; Förstmann, Ruben (Procedia CIRP, 2014)
Due to cost pressure, shortened development cycles as well as increasing variety and technical product complexity companies face more complex parallel development processes. Especially during ramp-up this leads to huge difficulties regarding the management and coordination of the departments involved across company and supply chain. To overcome these difficulties and to cut down timelines for development Modular Production Architectures (MPA) have shown evidence to be a useful management-tool during ramp-up. The implementation of this three step methodology is the main subject of this paper. At first a range of product types and general processes are determined for which the MPA should be relevant. In addition, the relevant processes with potential requirements to product design need to be identified. As a second step, the ideal production process is identified by investigating process alternatives for the MPAs’ range company-wide. All current production processes and equivalent alternatives are evaluated through expert interviews and assessed by their capabilities and standardization potentials. Thirdly, for each best-practice sub-process boundary conditions of process parameters are identified and transferred into product design requirements. By implementing this approach companies are enabled to ramp-up new products in less time with lower costs due to an effective management- support of the MPA-process.